Estimate Zinc-Oxide Particles on PMMA Mechanical Properties - Muhsin, Saja Ali; Hummudi, Israa Mohammed; Al-Ani, Makarem A.R. (Journal of Techniques, 2022)
Background: Poly-methylmethacrylate is the most used dental material for the construction of removable prosthodontic appliances. Unfortunately, it has shown to be lacking two important properties which are radio-opacity and mechanical strength. Zinc-oxide (ZnO) powder is widely used in dentistry and is considered a semiconductor material with the radio-opaque property. Purpose: To determine the effect of ZnO filler powder on some mechanical properties (impact and transverse strength) of microwave-cured acrylic denture base. Approach: The ZnO powder was added to the acrylic polymer powder in two percentages of 2% and 4% by weight. The prepared sample of acrylic resin was evaluated with impact and transverse strength (n=10). ANOVA and Tukey test were used at a P-value of (P≤0.05). Results: Significant reduction in the transverse strength was noticed in the acrylic denture base with the incorporation of ZnO powder as a filler material in both concentrations. However, non-significant differences were observed in the impact strength with the incorporation of the ZnO filler agent. Conclusions: The addition of ZnO radio-opacifier powder as a filler agent could affect the properties (impact and transverse strength) of microwave-cured acrylic resin.